Amperometric micro pH measurements in oxygenated saliva - Chaisiwamongkhol, K; Batchelor-McAuley, C; Compton, R (Royal Society of Chemistry, 2017)
An amperometric micro pH sensor has been developed based on the chemical oxidation of carbon fibre surfaces (diameter of 9 µm and length of ca. 1 mm) to enhance the population of surface quinone groups for the measurement of salivary pH. The pH analysis utilises the electrochemically reversible two-electron, two-proton behaviour of surface quinone groups on the micro-wire electrodes. A Nernstian response is observed across the pH range 2-8 which is the pH range of many biological fluids. We highlight the measurement of pH in small volumes of biological fluids without the need for oxygen removal and specifically the micro pH electrode is examined by measuring the pH of commercial synthetic saliva and authentic human saliva samples. The results correspond well with those obtained by using commercial glass pH electrodes on large volume samples.